Pemikiran Pendidikan Akhlak Ibnu Maskawaih dan Relevansinya dalam Pendidikan Akhlak di MTs Islamiyah Kepung - Ahmad Masrukin; Nila Nur Hikmah (Program Studi Manajemen Pendidikan Islam, 2024)
Ibnu Maskawaih is an intellectual in the field of moral philosophy. Ibn Maskawaih's moral philosophy thoughts do not hinder them and may even be able to provide motivation and great influence for the existence of renewal thoughts in Islam, especially in moral education. Based on the thoughts above, the author considers that it is important to study the title